Building floorspace and stock measurement: A review of global efforts, knowledge gaps, and research priorities - Minda Ma; Shufan Zhang; Junhong Liu; Ran Yan; Weiguang Cai; Nan Zhou; Jinyue Yan (Nexus)
Despite a substantial body of research—evidenced by our analysis of 2,628 peer-reviewed papers—global building floorspace data remain fragmented, inconsistent, and methodologically diverse. The lack of high-quality and openly accessible datasets poses major challenges to accurately assessing building carbon neutrality. This review focuses on global building floorspace, especially its nexus with energy and emissions. The key research areas include energy modeling, emissions analysis, building retrofits, and life cycle assessments. Each measurement approach—top down, bottom up, and hybrid—has its own limitations; top-down methods provide broad estimates but low accuracy, whereas bottom-up approaches are more precise but data intensive. Our simulations reveal a surge in floorspace growth across emerging economies, most notably in India, Indonesia, and Africa, with India’s per capita floorspace projected to triple by 2070. We emphasize the need for a high-resolution global floorspace imagery database to compare energy efficiency, track decarbonization progress, and assess renovation impacts while promoting building sufficiency and accelerating the transition to net-zero building systems. Broader context: The International Energy Agency announced that the building sector, which is responsible for nearly 40% of global energy consumption and carbon emissions, now faces a significant challenge: the lack of comprehensive data on building floorspace. This data gap hampers accurate measurement of carbon intensity and limits the ability to assess decarbonization strategies throughout the building life cycle. Global efforts to reduce building-related emissions are constrained by fragmented data and methodological limitations. The complexity of quantifying floorspace across diverse building typologies and regional contexts further complicates carbon accounting and mitigation comparisons. This study examines the influence of floorspace on building energy consumption and carbon emissions across all life cycle stages, categorizing existing floorspace measurement approaches and highlighting their strengths and limitations. It also assesses the current global status of building floorspace and provides future projections of the building stock. This study highlights the urgent need for a high-resolution global floorspace imagery database, which would enable more accurate comparisons of energy efficiency, decarbonization progress, and renovation impacts. Additionally, it highlights the importance of building sufficiency—designing and operating buildings to minimize environmental impacts by prioritizing efficiency, downsizing and simple living, optimal space utilization, and reduced resource consumption—as a key strategy for promoting low-carbon, sustainable development in the building sector.